Formação continuada de educadores em escolas de governo: conceitos e práticas do Estado de São Paulo - Alves, Ana Panzani (2014)
This research, conducted as part of the Post-graduation Program in Education: Curriculum, under the research line of New Technologies in Education, presents a study aimed to examine whether there are similarities between federal and state public policies of continued teachers training and how is the use of Information and Communication Technologies (ICT) in the State of São Paulo's practices from 2009 to 2013, in the context of Escola de Formação e Aperfeiçoamento dos Professores do Estado de São Paulo "Paulo Renato Costa Souza" of Secretaria da Educação of São Paulo State (SEE-SP). This research is theoretically grounded in the thought of Álvaro Vieira Pinto, Paulo Freire and researches of Gatti, Barreto, Tedesco, Saviani, Sacristán and Fernando Almeida, as regards: the concept of technology as a human construction and as a human right; the dialogical relationship as a space of knowledge construction; and continued teachers training as basis to the teaching practice. Were collected and analyzed public policies of continued teachers training and public data of the continued trainings courses offered by EFAP in the period from 2009 to 2013. This study suggests that there is a convergence between public policies for continued teachers training and the practice of State of São Paulo, as well as ICT are widely used to meet more than 280.000 professionals from SEE-SP geographically distributed throughout the state by promoting the ownership of ICT by educators, the training context and exchange among peers from different schools and regional administrations distant from each other